6.7k views
0 votes
Solve for x:16^(4x-3)=8^(2x+4)

User Geon
by
5.3k points

1 Answer

3 votes

Answer:

x = 2.4

Explanation:

16^(4x - 3) = 8 ^ (2x + 4)

16 = 2^4

8 = 2^3

2 ^ 4*(4x - 3) = 2^3(2x + 4)

Since the bases are the same, you can equate the powers

4(4x - 3) + 3*(2x + 4) Remove the brackets.

16x - 12 = 6x + 12 Subtract 6x from both sides

16x - 6x - 12 = 12 Combine the terms on the left

10x - 12 = 12 Add 12 to both sides

10x = 24 Divide by 10

x = 2.4

User Sergey Kolesnik
by
4.9k points